Kritik Misbah Musthofa dalam Tafsir al-Iklil Terhadap Kebijakan Program KB di Era Orde Baru - Ahmad, Nehru Millat (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2022)
Abstract In this paper, we will discuss the interpretation of Misbah Musthofa's work entitled al-Iklil fi Ma'ani al-Tanzil. In this interpretation using the tahlili method and the style of this interpretation when viewed from several opinions it has several features, but in this writing the author includes the Sufistic style and adab al-Ijtima'i. In interpreting a verse Misbah Musthofa goes through a lot of ratios (bi al-Ray'i). The purpose of writing this commentary is so that people are always guided by the Qur'an in life in the world. In addition, this interpretation also criticizes a lot of problems or events that occur in the midst of society. As the author gave an example of the ban on family planning according to Misbah Musthofa by linking the incident to the story of Pharaoh. The result of this study is the interpretation of al-Iklil fi Ma'ani al-Tanzil is one of the interpretations with an archipelago nuance with its interpretation using the Javanese Pegon script. In his interpretation, Misbah Musthofa always explains the meaning of the verse clearly and in detail, for example the relationship of a verse with verses and hadiths. However, when including a history of hadith, Misbah Musthofa does not include the sanad of the hadith.